Analisis Gaya Kepemimpinan di PT. Sari Incofood Corporation - Simanjuntak, Marihot; Bahri, Syamsul (Universitas Muhammadiyah Tapanuli Selatan, 2024)
In this instance, researchers discovered that poor communication frequently happens between managers and staff. Leaders typically exhibit dominance, with little employee involvement, and make all decisions for the good of the organization. This style of leadership works better in newer firms where the hired staff members are experts in their disciplines and lack much experience performing their jobs. This study employs a qualitative methodology. Research on the circumstances of natural things is done using qualitative research, which is grounded on postpositivism. Use triangulation data collection methods, inductive or qualitative data analysis, and a focus on meaning rather than generalization. A qualitative approach is a kind of research wherein core and story analysis is conducted without the use of data, circumstances, descriptions, or in-depth interviews. The interview's findings indicate that employees' input is still not included when making decisions, which reduces their sense of independence. The capacity for motivation is excellent since it provides rewards annually and supports staff members in the event of difficulties. Direct communication skills are also excellent, although they are frequently misinterpreted when conveyed through the media. At PT Sari Incofood Corporation, a blended leadership style is adopted to raise staff performance. Performance metrics demonstrate how an autocratic leadership style can enhance worker performance, and decision-making that puts the leader's preferences ahead of those of the workforce is indicative of this type of leadership.Kata kunci:Â Kepemimpinan, Komunikasi, Kinerja Karyawan